Audit Data Warehouse System using COBIT 5 Framework - Sri Utami, Komang; Wira Darma, I Gede; Sudarma, Made (International Journal of Engineering and Emerging Technology, 2019)
Udayana University has now implemented an integrated information system that covers ongoing business processes by involving all components of the academic community. All data circulating in the integrated system leads to the Data Warehouse (DWH). DWH has a goal as a data integration system, report generation, data analysis, and executive information provider. With the importance of the application of this DWH and the frequent problems that are inaccuracies in the data generated by the system, an audit is needed to evaluate the system, assess system capabilities and make recommendations for improvements so that it can support the achievement of system objectives. Audits conducted using the COBIT 5 framework are focused on the purpose of providing IT services according to business needs. This study focuses on evaluating one of COBIT 5's business objectives, namely Optimization of business process functions, which involves 5 domains consisting of 28 processes and acquired capability value which is 3.04 which states that the implementation of IT services has gone well, has been established and has standards